The Association between Intertwin Difference in First Trimester Crown-Rump Length, Nuchal Translucency, and Birth Weight Discordance in Twin Pregnancies: A Retrospective Cohort Study. (17th November 2022) - Ferraro, Zachary Michael; Zhang, Tinghua; Moretti, Felipe; Fung-Kee-Fung, Karen
Abstract : Background. Discordant birth weight in twins is linked to poor outcomes and predicting this discrepancy may lead to enhanced screening and surveillance. Our purpose was to quantify the relationship between intertwin nuchal translucency (NT) and crown-rump length (CRL) discordance with birth weight discrepancies ≥ 20%. Methods. We conducted a retrospective cohort study of 887 live twin births delivering at a Canadian tertiary care center over a 7-year period who opted for integrated prenatal screening. Categorical data are presented as numbers and percentages, and continuous data are expressed as means and standard deviations. Chi-square tests, Fisher's Exact tests, or T -test were performed as appropriate. We then used published data and receiver operating curves to determine the optimal thresholds for predicting birth weight discordance based on first trimester intertwin NT differences. These values were used in multivariate logistic regression models accounting for known confounders. Results. Roughly 16% of twin pairs exhibited ≥ 20% difference in birth weight. Twin pairs with a CRL discordance greater than 10% have nearly a 4 times greater likelihood of having a birth weight discordance greater than 20% (OR 3.71, CI 2.24-6.14) while controlling for chorionicity, maternal age, gestational age at delivery, maternal body mass index (BMI), and parity. In these models, intertwin NT discordance ≥ 20% (OR 1.16, CI 0.77-1.77) and NT discordance ≥ 14% (OR 1.08, CI 0.73-1.60) were not statistically significant predictors of twin birth weight differences. However, when evaluating the effect of the larger intertwin NT value corresponding to the 95 th percentile, an NT difference ≥ 0.9 mm was predictive of birth weight discordance ≥ 20% (OR 2.53, CI 1.21-5.29). Conclusion. Although intertwin CRL and NT discordance measured via ultrasound between 11-14 weeks gestation are related to birth weight discordance, there is uncertainty as to whether twin birth weight differences are related to adverse pregnancy outcomes in this population.